Determination of Ship Accident Risk in Indonesia: Contribution of Crew Member Competence and Job Stress Through Safety Culture Moderated by Communication Effectivity and Supervision - Danny Faturachman; Edi Abdurachman; Prasadja Ricardianto; Siti Maemunah (International Journal of Marine Engineering Innovation and Research, 2026)
this paper investigates how human factor variables determine ship accident risk in Indonesian domestic shipping. Drawing on accident investigation reports and international literature, the study proposes and tests a structural model linking deck crew competence, supervisory quality, and work stress to perceived ship accident risk, with safety culture as an intervening variable and work stress and competence as moderators. National data from Indonesia’s National Transportation Safety Committee (KNKT) for 2020–2025 indicate that human error remains the dominant contributing factor in marine accidents, with high fatality rates despite the implementation of SOLAS, STCW, and the ISM Code. Relevant studies confirm that inadequate training, fatigue, miscommunication, and weak supervision are among the most critical contributors to marine casualties. A quantitative survey will be conducted among Indonesian seafarers working on domestic Roro ferries and passenger/ cargo vessels, focusing on major inter-island routes. The proposal model will be tested using Partial Least Square–Structure Equation Modelling (SEM) to assess direct, indirect, and moderating effects of competence and job stress on the relationship between safety culture and perceived accident risk. The expected contribution is twofold: theoretically, it integrates Human Factor Analysis and Classification System (HFACS) Maritime and safety culture perspectives into a comprehensive human factor risk perception framework tailored to an archipelagic developing country; practically, it provides evidence=based insights for regulators and shipping companies regarding priority interventions in crew training, work-rest scheduling, supervision, and safety culture development.